A Fuzzy Multi-Objective Multi-Period Common Weight Network DEA Model to Measure the Environmental Efficiency of Iran's Oil Refineries - Amineh Hosseini; Kaveh Khalili-Damghani; Ali Emami Meibodi (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2016)
In this paper, a methodology is proposed to measure the efficiency ofnational energy sector in IRAN. The technical and environmentalperformance of the oil refineries in IRAN as a major producer of energy andfuel are evaluated based on data from years 2010 to 2013. In this study, afuzzy multi-objective multi-period common weight network dataenvelopment analysis approach is proposed and customized to evaluate theperformance of oil refineries. A certain scenario, called food-production inwhich a refinery is assumed as a decision making unit (DMU) consuminginputs to produce outputs, is considered to evaluate the technical andenvironmental performance in presence of undesirable outputs. The maincontribution of this study are summarized as: (1) Proposing a multiobjectivecommon weight DEA model in order to determine the weights ofinputs and outputs in a single run; (2) Calculating the long term efficiencyscores during a multiple-periods of planning incorporating dynamic natureof inputs and outputs; (3) Handling a compromise solution using fuzzymathematical programming to address multi-objective mathematicalprogramming; (4) Proposing a linear mathematical programming to achievethe global optimum solutions; (5) Enhancing the discrimination power of theDEA models; (6) Reducing the computational time of modeling and solutionprocedure; (7) incorporating effective criteria in the modeling procedure.The analysis of case study presents the efficacy and applicability ofproposed method in comparison with existing classic models.